Characterization and mechanical properties of biocomposite of cantula fiber reinforced nano-ha/magnesium/shellac for bone screw material - Triyono, Joko; Utami, Dea Pawestry; Rahardjo, Wijang Wisnu; Nugroho, Fransiskus Bima Widi (Jurnal Teknosains, 2025)
Accidents are a major cause of fractures in Indonesia. One of treatments for fractures is bone screws with support plates that are placed on broken bone. Currently, many biomaterials for bone screws are being developed which have biodegradable properties so that post-operative bone healing is not required. The purpose of this study was to determine the effect of cantula fiber addition on tensile strength, wear rate, and crystallinity of nano-HA/magnesium/Shellac biocomposite for bone screw materials. Nano-HA/magnesium/Shellac/cantula fiber materials were mixed using a blender. The material was mixed with a magnesium/hydroxyapatite ratio of 70/30 and cantula fiber is added with variations of 0%, 10%, 20% and 30% of total volume. After that, the material mixture was compacted with a pressure of 300 MPa for 10 minutes. Then the sintering process was carried out at a temperature of 140 ̊C for two hours. The results showed that the highest tensile strength value was 7.86 MPa at 30% variation. The lowest wear rate was 0.31 x 10-3 mm3/Nm at 30% variation. The highhest crystallinity in XRD observations was obtained at 30% variation, which was 79.65%.